Study on Sugeno Probability Integral of γ-fuzzy Operator - ZHAO Hui; SHAN Yunxiao; JIANG Xinge (Journal of Harbin University of Science and Technology)
As an indispensable branch of fuzzy mathematics, fuzzy probability integral is an important integral form that relies on fuzzy probability and fuzzy measure, and is also a powerful tool for studying fuzzy mathematics. Aiming at the definition and theorem research of fuzzy probability, fuzzy measure and its integral, two kinds of ideal γ－fuzzy operator form is given, which proves that the condition of triangular norm operator is satisfied; And under the background of the proposed relevance measure space, the definition and theorem of generalized Sugeno probability integral are given, verification of a number of theorems that satisfy the condition to prove its feasibility.